Pria sebagai Privileged Allies dalam Gerakan Feminis HeForShe untuk Memperjuangkan Hak Pekerja Wanita di Indonesia (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: Gender inequality is a problem faced throughout the world, including in Indonesia, where the patriarchal system causes women to often get injustice from various sectors, especially the work sector. In 2014, UN Women initiated the formation of HeForShe by making men as agents of change so that women can live equally without discrimination. This research then aims to see why the HeForShe organization involves men in efforts to address gender inequality in Indonesia. This research also uses qualitative methods with various data sources from the HeForShe organization, the Government of Indonesia and the Ministry of PPPA. The theory used is Liberal Feminists with the concept of men as privileged allies. The results of this study indicate that men as privileged allies in the struggle for the rights of women workers in Indonesia. The support provided by Indonesian men currently varies from learning about gender equality to building movements to support the elimination of violence against women. It is through this contribution that women's voices will be heard and gender equality actions will be better realized. Keywords: Indonesia, Gender Inequality, HeForShe, Privileged Allies, Equality, Rights of Women Workers Abstrak: Ketidaksetaraan gender merupakan permasalahan yang dihadapi di seluruh dunia termasuk di Indonesia dimana sistem patriarki menyebabkan wanita seringkali mendapatkan ketidakadilan dari berbagai sektor terutama sektor pekerjaan. Pada tahun 2014, UN Women menginisiasikan terbentuknya HeForShe dengan menjadikan pria sebagai agen perubahan agar wanita bisa hidup setara tanpa diskriminasi. Penelitian ini kemudian bertujuan untuk melihat mengapa organisasi HeForShe melibatkan pria dalam upaya penanganan ketidaksetaraan gender di Indonesia. Penelitian ini juga menggunakan metode kualitatif dengan berbagai sumber data dari organisasi HeForShe, Pemerintah Indonesia serta KemenPPPA. Teori yang digunakan adalah Feminis Liberal dengan konsep pria sebagai privileged allies. Hasil dari penelitian ini menunjukkan bahwa pria berperan sebagai privileged allies dalam perjuangan hak pekerja wanita di Indonesia. Dukungan yang diberikan pria Indonesia saat ini sangat beragam mulai dari mempelajari mengenai kesetaraan gender sampai membangun gerakan untuk mendukung penghapusan kekerasan terhadap wanita. Melalui kontribusi inilah suara wanita akan lebih didengar dan kesetaraan gender akan terwujud dengan lebih baik. Kata Kunci: Indonesia, Ketidaksetaraan Gender, HeForShe, Privileged Allies, Kesetaraan, Hak Pekerja Wanita.